Reconceptualizing Islamic Calendar Determination: An Integrative Ushul Fiqh and Astronomical Approach - Amrin; Muhammad Dwi Fajri; Eman Suherman; Mas’udatul Fitriyah; Ishma Amelia (Faculty of Sharia, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The process of determining dates for Islamic lunar calendar, especially the onset of Hijri months, is a crucial yet contentious topic among Muslims around the world due to conflicting approaches, namely hisab and rukyat, which differ in methodology. Apart from the conflict that these differences create in terms of synchronizing religious rituals, other issues such as legal authority, epistemology, and social cohesiveness are implicated. The present study seeks to generate a new methodology by integrating principles of Ushul Fiqh with modern astronomy techniques in order to resolve the conflicts.Using the qualitative literature-based approach, the present study analyzes classical and modern sources on Islamic jurisprudence and astronomy from the perspective of theology and philosophy. The principles of Ushul Fiqh, namely taḥqīq al-manāṭ, maṣlaḥah, and ijtihād, are used to analyze the epistemology and application of the aforementioned methodologies.It was concluded that an integrative methodology based on theprinciples of Ushul Fiqh offersa flexible theoretical and practical framework that is able to legitimize the two approaches while accounting for contemporary problems, including technological advances and international coordination.This study offers both theoretical and practical contributions by proposing a harmonized model for Islamic calendar determination that aligns scientific accuracy with Sharia principles. It further provides strategic insights for scholars, fatwa institutions, and policymakers seeking to advance a more unified and globally relevant Islamic calendar system.